Hidden Within: Pulmonary Nocardiosis in an Immunocompetent COPD Patient - Rodriguez-Ramos, Joel; Rodriguez-Cintron, William (Puerto Rico Health Sciences Journal, 2025)
This report presents the case of an 86-year-old man with chronic obstructive pulmonary disease (COPD) managed since 2018 with inhaled corticosteroids, long-acting muscarinic antagonists, long-acting beta-agonists, and roflumilast. He was admitted to the medical intensive-care unit with acute respiratory failure due to severe pneumonia. Imaging revealed left lower lobe consolidation. Despite treatment with piperacillin/tazobactam and methylprednisolone, his condition worsened, necessitating bronchoscopy. Sputum samples identified Nocardia species, confirming pulmonary nocardiosis, and he was started on trimethoprim-sulfamethoxazole (TMP-SMX) therapy. The case highlights the risks associated with long-term corticosteroid use in COPD patients, which may predispose them to opportunistic infections such as nocardiosis. The patient’s severe COPD and potential macrophage dysfunction likely contributed to the development of nocardiosis This case underscores the importance of the early recognition and appropriate treatment of pulmonary nocardiosis to reduce associated morbidity. Bronchoscopy is crucial for diagnosing difficult-to-culture organisms in patients unresponsive to standard treatment, and gene sequencing offers promise for rapid, accurate detection. The patient showed clinical improvement with TMP-SMX therapy, with follow-up imaging indicating partial resolution. Continued outpatient care is scheduled, emphasizing vigilance in managing high-risk COPD patients, particularly in tropical regions such as Puerto Rico.